Problematic of the constitution drafting and its application in culturally diverse and politically transformed societies (Iraq after 2003 as a model) - Al-Deen , Najm Al-Deen Muhyi; Sheekho, Renjibar Jameel (The International and Political Journal, 2023)
The task of drafting a constitution in multi-cultural societies, that are witnessing major political transformations, is one of the issues that raises many problems in this transitional phase of their political life, especially if these constitutions are unable to objectively express the reality of their societies in a desired change, reform, and development. Iraq (the subject of our research) is one of these countries that suffer from such a problem after the change it witnessed in 2003. The research is an attempt to diagnose the nature, causes, dimensions, and effects of this problem and its repercussions on the overall political and societal life in Iraq. To achieve this goal, we have raised a few questions regarding the re-constitutionalizing political life and institutionalizing politics. In other words, the governance of the ruling system. Hence, this research also acquires its theoretical (scientific) and realistic (objective) importance. It seeks to filter the constitutional text from its formal and theoretical templates, by comparing this text to reality and showing the outcome of this process.